2014
DOI: 10.1016/j.kjms.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p38 mitogen‐activated protein kinase in acquired gemcitabine‐resistant human urothelial carcinoma sublines

Abstract: Resistance to chemotherapeutic drugs is one of the major challenges in the treatment of cancer. A better understanding of how resistance arises and what molecular alterations correlate with resistance is the key to developing novel effective therapeutic strategies. To investigate the underlying mechanisms of gemcitabine (Gem) resistance and provide possible therapeutic options, three Gem-resistant urothelial carcinoma sublines were established (NG0.6, NG0.8, and NG1.0). These cells were cross-resistant to arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Resistance to chemotherapeutic drugs is one of the major challenges in the treatment of cancer. Inhibition of p38 significantly increased Gemcitabine sensitivity in bladder cancer cells [33]. Fang, Y et al reported that JNK inhibitor SP600125 suppressed anchorage-independent growth of T24T bladder cancer cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to chemotherapeutic drugs is one of the major challenges in the treatment of cancer. Inhibition of p38 significantly increased Gemcitabine sensitivity in bladder cancer cells [33]. Fang, Y et al reported that JNK inhibitor SP600125 suppressed anchorage-independent growth of T24T bladder cancer cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, suppression of the MEK-ERK signaling pathway by PD98059 increased rather than decreased cisplatin resistance (28). In addition, inhibition of p38 MAPK significantly reduced gemcitabine sensitivity in NTUB1 cells, and Calebin-A enhanced the cytotoxicity of vincristine in SGC7901/vincristine cells through the inhibition of JNK (29,30). The exact effect of the modulation of MAPKs depends on the cell types and crosstalk among the various pathways.…”
Section: Discussionmentioning
confidence: 99%
“…P-38 has an important function in cell-cell signaling against stress and is responsive to stress stimuli, such as cytokines, ultraviolet irradiation, heat shock, and osmotic shock. It is also involved in cell differentiation, apoptosis, and autophagy [36,37]. Similarly, NF-kB plays a very important role in several cellular functions.…”
Section: Resultsmentioning
confidence: 99%